The inclusion of psychological factors in the evaluation of a curriculum enrichment program for students with high ability - Aperribai, Leire; Moreno, Garbiñe; Sarrionandia, Ainize; Salaberria, Karmele (Frontiers in Psychology, 2025)
There is currently evidence of the importance of some psychological factors in long-term academic performance. In this study, the impact that a curriculum enrichment program has had on academic performance has been evaluated considering psychological variables related to academic performance. A quasi-experimental study of two groups (experimental and control), based on a design of repeated measures was carried out. Participants were students with high ability of 5 and 6 years of Primary Education and 1 and 2 years of Secondary Education of 9 educational centers, aged between 9 and 13 years old, being 68% boys and 32% girls. Psychological variables such as self-esteem (Rosemberg Self-Esteem Scale), learning approach (Revised Survey of Study Processes), and creativity (Test CREA), as well as academic achievement or performance (academic scores) were assessed to evaluate the curriculum enrichment program Sakonduz. Results show that, in respect to academic achievement, the experimental group unexpectedly worsened while the control group improved, but in both cases the differences were not significant. As for the learning approach, the control group didn't show any changes, as expected, while the experimental group maintained the deep motivation approach (DM) and decreased the deep strategy approach (DS), and consequently the deep learning general approach (DA). Also, the results showed a considerable decrease in the level of self-esteem of the control group, while it was maintained at the same high level in the experimental group. Finally, creativity measurements didn't have consistent results. This curricular enrichment program should be implemented as a long-term and more intense program to obtain more evidence of its effect on psychological aspects. Nevertheless, an important attrition occurred, and it would be important for the future the implication of the schools and teachers to implement and collect more evidence of the program's effectiveness.